2021
DOI: 10.1042/cs20210128
|View full text |Cite
|
Sign up to set email alerts
|

IGF2 deficiency causes mitochondrial defects in skeletal muscle

Abstract: Exercise training improves muscle fitness in many aspects, including induction of mitochondrial biogenesis and maintenance of mitochondrial dynamics. The insulin-like growth factors were recently proposed as key regulators of myogenic factors to regulate muscle development. This study aimed to investigate the physical exercise impact on insulin-like growth factor 2 (IGF2) and analyzed its functions on skeletal muscle cells in vitro. Using online databases, we stated that IGF2 was relatively highly expressed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…Still, several genes encoding proteins known to induce mitochondrial biogenesis have been shown to increase expression after exercise, e.g., CAMK2A and CAMK2B (Table S 1 ) [ 22 , 23 ]. A recent study indicates that IGF2 also promotes mitochondrial biogenesis in skeletal muscle [ 24 ], and similar results have been obtained for IGF1 [ 25 27 ], and both transcripts increase after exercise (Table S 1 ). Although pathways for mitochondrial biogenesis were not over-represented after the intervention, those involved in vasculogenesis and angiogenesis were highly upregulated with resistance training.…”
Section: Discussionsupporting
confidence: 81%
“…Still, several genes encoding proteins known to induce mitochondrial biogenesis have been shown to increase expression after exercise, e.g., CAMK2A and CAMK2B (Table S 1 ) [ 22 , 23 ]. A recent study indicates that IGF2 also promotes mitochondrial biogenesis in skeletal muscle [ 24 ], and similar results have been obtained for IGF1 [ 25 27 ], and both transcripts increase after exercise (Table S 1 ). Although pathways for mitochondrial biogenesis were not over-represented after the intervention, those involved in vasculogenesis and angiogenesis were highly upregulated with resistance training.…”
Section: Discussionsupporting
confidence: 81%
“…6 C). An in vitro study has demonstrated the potential involvement of IGF2 in improving the mitochondrial structure of muscle cells in the culture medium [ 44 ]. Thus, these findings suggest that IGF2 treatment can improve the mitochondrial function of oocytes from obese mice by somehow improving mitochondrial ultrastructure.…”
Section: Resultsmentioning
confidence: 99%
“…IGF2 is a promyogenic protein that is important for muscle development as well as fetal and post-natal growth, and it also functions in muscle recovery and nerve regeneration after injury ( 18 ). IGF2 deletion in skeletal muscle cells reduces mitochondrial biogenesis, mitochondria-associated protein content, and mitochondrial function ( 40 ). Studies have also shown that increased IGF2 expression promotes the intramuscular lipid content of porcine skeletal muscle ( 20 ).…”
Section: Discussionmentioning
confidence: 99%